Background of the accreditation of the faculty of law 2015 - Esquivel Salas, Hernán (2015)
This article develops the background of the accreditation process of the Faculty of Law of the University of Costa Rica. The previous stages and the first attempts at self-evaluation and self-regulation, as well as the beginning of the path of accreditation (which was acquired in 2015) are described. Thus, efforts to achieve accreditation have become a positive action taken by the various authorities of the School for several years, until finally this objective was achieved.